2021
DOI: 10.1245/s10434-021-10346-x
|View full text |Cite
|
Sign up to set email alerts
|

Esophagectomy or Total Gastrectomy for Siewert 2 Gastroesophageal Junction (GEJ) Adenocarcinoma? A Registry-Based Analysis

Abstract: Backgrounds Due to a lack of randomized and large studies, the optimal surgical approach for Siewert 2 gastroesophageal junctional (GEJ) adenocarcinoma remains unknown. This population-based cohort study aimed to compare survival between esophagectomy and total gastrectomy for the treatment of Siewert 2 GEJ adenocarcinoma. Methods Data from the National Cancer Database (NCDB) from 2010 to 2016 was used to identify patients with non-metastatic Siewert 2 GEJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 41 publications
0
18
0
10
Order By: Relevance
“…ACGEJ is divided into three subtypes (Siewert type I, II, and III) according to the Siewert classification and proximal/distal of the anatomic gastric cardia and the overall survival of the three subtypes were different. The prognosis of ACGEJ is related to several factors, including the extent of nodal involvement (4,5), human epidermal growth factor re-ceptor 2 (HER2) status (6), neoadjuvant chemotherapy, and surgical strategy (7,8). More numbers of resected lymph nodes were associated with better survival in Siewert type II ACGEJ patients (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACGEJ is divided into three subtypes (Siewert type I, II, and III) according to the Siewert classification and proximal/distal of the anatomic gastric cardia and the overall survival of the three subtypes were different. The prognosis of ACGEJ is related to several factors, including the extent of nodal involvement (4,5), human epidermal growth factor re-ceptor 2 (HER2) status (6), neoadjuvant chemotherapy, and surgical strategy (7,8). More numbers of resected lymph nodes were associated with better survival in Siewert type II ACGEJ patients (5).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of ACGEJ is related to several factors, including the extent of nodal involvement ( 4 , 5 ), human epidermal growth factor receptor 2 ( HER2 ) status ( 6 ), neoadjuvant chemotherapy, and surgical strategy ( 7 , 8 ). More numbers of resected lymph nodes were associated with better survival in Siewert type II ACGEJ patients ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…21 Recent large-scale studies suggest no difference in post-operative morbidity although oesophagectomy was associated with better overall survival than gastrectomy. 22,23 It remains necessary for these data to be evaluated in a randomized control setting.…”
Section: Discussionmentioning
confidence: 99%
“…While an extended gastrectomy with a transabdominal approach avoids the pulmonary complications associated with a thoracotomy, 20 it compromises the extent of thoracic lymphadenectomy and is associated with a higher rate of microscopic residual tumour (R1) 21 . Recent large‐scale studies suggest no difference in post‐operative morbidity although oesophagectomy was associated with better overall survival than gastrectomy 22,23 . It remains necessary for these data to be evaluated in a randomized control setting.…”
Section: Discussionmentioning
confidence: 99%
“…The present study 3 included patients with non-metastatic Siewert II GEJ adenocarcinoma receiving either esophagectomy ( n = 999) or total gastrectomy ( n = 8595), from the National Cancer Database (NCDB) from 2010 to 2016. This national population-based cohort study from the US demonstrated that patients receiving esophagectomy had significantly longer survival than total gastrectomy for Siewert II GEJ adenocarcinoma.…”
Section: Presentmentioning
confidence: 99%